GRAND-4: the German retrospective analysis of long-term persistence in women with osteoporosis treated with bisphosphonates or denosumab. Issue 10 (October 2016) - Hadji, P.; Kyvernitakis, I.; Kann, P.; Niedhart, C.; Hofbauer, L.; Schwarz, H.; Kurth, A.; Thomasius, F.; Schulte, M.; Intorcia, M.; Psachoulia, E.; Schmid, T.
Abstract Summary This retrospective database study assessed 2-year persistence with bisphosphonates or denosumab in a large German cohort of women with a first-time prescription for osteoporosis treatment. Compared with intravenous or oral bisphosphonates, 2-year persistence was 1.5–2 times higher and risk of discontinuation was significantly lower (P  < 0.0001) with denosumab. Introduction Persistence with osteoporosis therapies is critical for fracture risk reduction. Detailed data on long-term persistence (≥2 years) with bisphosphonates and denosumab are sparse. Methods From the German IMS® database, we included women aged 40 years or older with a first-time prescription for bisphosphonates or denosumab between July 2010 and August 2014; patients were followed up until December 2014. The main outcome was treatment discontinuation, with a 60-day permissible gap between filled prescriptions. Two-year persistence was estimated using Kaplan–Meier survival curves, with treatment discontinuation as the failure event. Denosumab was compared with intravenous (i.v.) and oral bisphosphonates separately. Cox proportional hazard ratios (HRs) for the 2-year risk of discontinuation were calculated, with adjustment for age, physician specialty, health insurance status, and previous medication use. Results Two-year persistence with denosumab was significantly higher than with i.v. or oral bisphosphonates (39.8 % [n  = 21, 154] vs 20.9 % [i.v. ibandronate;n  = 20, 472] and 24.8 % [i.v. zoledronic acid;n  = 3966] and 16.7–17.5 % [oral bisphosphonates;n  = 114, 401]; allP  < 0.001). Patients receiving i.v. ibandronate, i.v. zoledronic acid, or oral bisphosphonates had a significantly increased risk of treatment discontinuation than did those receiving denosumab (HR = 1.65, 1.28, and 1.96–2.02, respectively; allP  < 0.0001). Conclusions Two-year persistence with denosumab was 1.5–2 times higher than with i.v. or oral bisphosphonates, and risk of discontinuation was significantly lower with denosumab than with bisphosphonates. A more detailed understanding of factors affecting medication-taking behavior may improve persistence and thereby reduce rates of fracture.